Occupational Licensing in the Building Industry - Homer Clark (Washington University Law Quarterly, 1952)
Many articles have lately been written about the great increase in licensing laws in the various states, some of them taking the position that such laws are unnecessary, even harmful, and one writer judging them to be evidence of a return to a sort of guild system. This paper is an attempt at investigating licensing laws as they apply to the building industry, in the hope of drawing some conclusions as to their effect on the economy of that industry. The investigation starts from an assumption that the mere fact that licensing statutes are numerous is not necessarily an objection to them, and the fact that they sometimes apply to the humbler callings does not automatically indicate their absurdity. The statutes to be discussed are those having a regulatory, as distinguished from a taxing, function, although it is recognized that the regulatory statutes usually include an incidental tax. The distinguishing mark of such regulatory statutes is the inclusion of conditions to the acquisition of a license other than the mere payment of a fee. To some extent this distinction is arbitrary, since the payment of a fee of any size may be a substantial restriction upon entry into the trade, and in that sense be regulatory, but it is usually enacted for other purposes, and raises other problems. On the other hand some of the regulatory statutes may have incidental revenue-collecting purposes.
Keywords: Licenses